The effect of various clover management practices on gaseous N losses and mineral N accumulation - Aulakh, M. S., author; Rennie, D. A., author; Paul, E. A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1963)
A 2-yr field study was carried out to assess gaseous losses of N as N2O + N2 from two Black Chernozemic soils, where during year 1 wheat was underseeded to clover and in year 2, the clover in late June was (a) green-manured and the field fallowed, (b) harvested for hay and then fallowed, or (c) harvested for hay and allowed to regrow. Gaseous losses during year 1 were small and ranged from 1.3 kg N∙ha−1 (Blaine Lake clay loam) to 4.7 kg N∙ha−1 (Hoey clay loam). Gaseous losses were somewhat higher during the second year, but differences between the various clover management practices were generally small. The contribution of lower soil horizons towards gaseous nitrogen losses were shown to be negligible. Soil moisture, mean air temperature, nitrate + nitrite, and ammonia N concentrations collectively accounted for 37–66% of the variations in N2O fluxes. It is concluded that incorporation of clover followed by a partial fallow results in substantially less gaseous loss of nitrogen than the standard summerfallowing practice, and at the same time significantly increases mineral nitrogen accumulation in the soil.
Keywords: denitrification; nitrification; acetylene inhibition technique; mineralization; green manuring